Assessment of the genetic diversity of Argentinean isolates of Beauveria bassiana (Ascomycota: Hypocreales) using ISSR markers - Toledo, Andrea Vanesa (2019)
Recombination mediated through a parasexual cycle is a potential source of genetic diversity among mitosporic fungi such as Beauveria bassiana. Knowledge of this diversity is critical to understand the structure of the population. Therefore, the aim of this study was to analyze the genetic diversity within 36 Argentinean isolates of B. bassiana collected from different geographical regions and insect hosts; and to assess by means of ITS sequences the preliminary taxonomic position of the isolates that might be related to the phenotypic and genotypic differences. The results demonstrate that the fingerprints generated with four ISSR markers were enough to detect significant genetic diversity among Argentinean isolates, which was unrelated neither with the geographical origin nor with insect hosts.